Circadian Rhythmicity in Excised Samanea Pulvini: II. Resetting the Clock by Phytochrome Conversion - Simon, Esther (1976)
Excised Samanea saman pulvini were incubated in H(2)O or 50 mm sucrose in darkness for 100 to 152 hours except for brief exposures to red or far red light, and angles of opening measured periodically. When pulvini are incubated in H(2)O, the rhythm damps in the open position after two to three cycles irrespective of the light treatments, but when sucrose is available, the now persistent oscillations show large red, far red-regulated effects on phase, amplitude, mesor slope, and entrainment. Single red light pulses rephase the rhythm, with a phase response curve that resembles that reported for other plants and animals; such rephasing is prevented by immediately subsequent far red light, indicating that phytochrome is the photoreceptor. Red light pulses repeated every 24 hours entrain the rhythm, and also prevent damping if presented at an appropriate part of the cycle.